(untitled) - Young, Robert J. (Boca Raton, 2011)
Thoroughly updated, Introduction to Polymers, Third Edition presents the science underpinning the synthesis, characterization and properties of polymers. The material has been completely reorganized and expanded to include important new topics and provide a coherent platform for teaching and learning the fundamental aspects of contemporary polymer science.
Cấu trúc pha và cấu trúc hình thái của vật liệu polymer,Hóa học và hóa lý polymer,Nhập môn khoa học và công nghệ vật liệu polymer
Keywords: Polymers,Polymerization,Polyme,Chất tạo thành Polyme